Региональный фактор развития политической культуры населения Украины - Стегний, А. (Социология: теория, методы, маркетинг, 2005)
The author of this article examines the regional factor influence on integration and energizing functions of political culture of the population of Ukraine. As a factor of influence on the abovementioned functions, the region is analyzed as a territorial organization of sociopolitical and sociocultural aspects of human community acti vity. The compatibility of common social and cultural values as well as the level of political solidarity is researched on the basis of historical identity, spatial and ter ritorial selfidentification, desirable vector of the region development connected with the opposition “nationally integrated — regionally autonomous” as well as the level of territorial community authoritarianism. On the grounds of findings the author con cludes about political culture of all regions of Ukraine that can be defined as inclined to the passive integration pattern with a certain inessential deviation.